Upper cervical spine instability due to pyogenic infection successfully treated by one stage posterior debridement and stabilization: Case Report and literature review - Konbaz,Faisal S.; Aleissa,Sami I.; Alhelal,Fahad H.; Abalkhail,Majed S.; Alamri,Asim J.; Saeed,Abdullah I.; Mohabbat,Asim F. (Journal of Musculoskeletal Surgery and Research)
Pyogenic osteomyelitis of the upper cervical spine is a rare condition associated with different clinical symptoms and signs. Previous studies have stressed the difficulties in making the diagnosis due to its unusual location and relatively rare occurrence. We hereby describe a case of a 65-year-old man with pyogenic infection of the craniocervical junction up to the axis with severe instability managed by posterior fusion from occiput to C6, an open biopsy from C1–C2 lesions and irrigation and debridement. On follow-up visit at two years, our patient had recovered completely. We present this case to show that the posterior approach without the anterior transoral approach is a valid surgical option in such cases. Additionally, we emphasize the importance of stabilization to successfully treat spine osteomyelitis and summarize the literature available discussing upper cervical spine infection treatment options.